FRI0501 CARDIOVASCULAR DISEASE RISK ASSESSMENT IN PATIENTS WITH FAMILIAL MEDITERRANEAN FEVER RELATED AMYLOIDOSIS. (2nd June 2020) - Romano, M.; Yilmaz, M.; Jackson, B.; Acikel, C.; Piskin, D.; Berard, R.; Demirkaya, E.
Abstract : Background: FMF is an autosomal recessive disorder. Systemic inflammation in autoinflammatory disorders cause secondary systemic AA amyloidosis, which has been suggested as an important contributing factor to the excess cardiovascular disease (CVD) risk in patients with FMF. Objectives: Our aim was to investigate the CVD-related clinical outcomes in patients with FMF-related amyloidosis and to define risk factors for CVD events (CVDEs). Methods: A cross-sectional evaluation with prospective follow-up of consecutive patients with FMF-related amyloidosis or other non-diabetic primary glomerulonephropathy (PGN) was performed. Patients were followed for CVDEs. Flow-mediated dilatation (FMD), FGF-23 levels, serum lipid levels, hsCRP, BMI and homeostasis model assessment (HOMA) were assessed. A Cox regression analysis was performed to evaluate the probability of CVDEs associated with each risk factor. Results: There were 107 patients in FMF-related amyloidosis group and 126 patients with PGN group. Forty-seven CVDEs were registered during the 4.2-years follow up; all 28 patients in the FMF-related amyloidosis versus 14/19 patients with PGN group who developed CVDEs before 40 years of age (P=0.002) (Figure 1). CVD mortality was 2.8 times higher (95% CI 1.02-7.76, p=0.03) in patients with FMF-related amyloidosis (n=12) than PGN (n=5). Mortality due to CVD was higher in patients less than 40 years old with amyloidosis than PGN (12/107 and 3/126 respectively, RR=4.71, 95% CI 1.36-16.25, p=0.006). Patients with CVDEs had higher levels of proteinuria, hsCRP and FGF23, and lower FMD compared to patients without CVDEs. Across both groups, FGF23 and FMD levels were independently associated with the risk of CVDEs (Table 1 ). Conclusion: Patients with FMF-related amyloidosis are at increased risk of CVDEs with early mortality age. These patients should be closely monitored and if inflammation is poorly controlled with colchicine, biological agents must be added to treatment even if they develop amyloidosis. We also found that hsCRP, FGF 23 and FMD levels were the strongest predictors of CVD risk in patients with FMF. These biomarkers can stratify risk of early CVD in patients with FMF-related amyloidosis. References: [1] Yilmaz, M.I., et al., Endothelial function in patients with familial Mediterranean fever-related amyloidosis and association with cardiovascular events. Rheumatology (Oxford), 2014. 53 (11): p. 2002-8. Disclosure of Interests: None declared